2006
DOI: 10.1164/rccm.200604-488oc
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Pulmonary Fibrosis

Abstract: Rationale and Hypothesis: Idiopathic pulmonary fibrosis is a fatal disease with a variable rate of progression. We hypothesized that changes in distance walked and quantity of desaturation during a six-minute-walk test (6MWT) would add prognostic information to changes in FVC or diffusing capacity for carbon monoxide. Methods: One hundred ninety-seven patients with idiopathic pulmonary fibrosis were evaluated. Desaturation during the 6MWT was associated with increased mortality even if a threshold of 88% was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(102 citation statements)
references
References 27 publications
2
97
1
Order By: Relevance
“…There is a strong relationship between reduced exercise capacity and increased mortality, particularly in IPF [10]. Exercise capacity is frequently a stronger predictor of prognosis than resting respiratory function [11,12]. There are multiple contributors to exercise limitation in ILD, with gas exchange limitation and circulatory limitation playing important roles.…”
Section: The Problemmentioning
confidence: 99%
“…There is a strong relationship between reduced exercise capacity and increased mortality, particularly in IPF [10]. Exercise capacity is frequently a stronger predictor of prognosis than resting respiratory function [11,12]. There are multiple contributors to exercise limitation in ILD, with gas exchange limitation and circulatory limitation playing important roles.…”
Section: The Problemmentioning
confidence: 99%
“…Undoubtedly, this mechanism plays a role, but it is unlikely to account for all cases of PH, for example the presence of PH in normoxemic IPF patients. Furthermore, intermittent nocturnal hypoxia and also exercise-induced desaturation, which are often present in IPF patients [8,35], might represent important factors in the development of disproportionate PH in these patients and need to be appropriately evaluated [36]. Interestingly, Pouwels-Fry et al [37] demonstrated that oxygen did not improve an exercise-induced increase in pulmonary artery pressure in IPF patients, suggesting that hypoxic vasoconstriction is not the only mechanism contributing to the acute increase in pulmonary pressure during exercise.…”
Section: Pathogenesismentioning
confidence: 99%
“…The most commonly used exercise tests are the 6-min walk test (6MWT) and cardiopulmonary exercise testing. Impaired gas exchange which worsens with exercise is a common feature in the pathophysiology of IPF and appears to have prognostic value as well [7,8,63]. When PH is present in the setting of IPF, common physiological abnormalities during exercise include decreased maximal oxygen consumption, increased dead space with progressive exercise and a low anaerobic threshold [64,65].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Defining intra-individual variability for D l CO is clinically important. Serial measurements of D l CO are commonly performed to assess disease activity in response to therapeutic interventions [11,12,13] and to monitor the effects of drug or toxin exposures [14,15,16]. …”
Section: Introductionmentioning
confidence: 99%